The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fneur.2022.1054624
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the progression of cerebral microbleeds in patients with concomitant cerebral small vessel disease

Abstract: Background and purposeSex differences in cerebral microbleeds (CMBs) are not well-known. We aimed to assess the impact of sex on the progression of CMBs.MethodsThe CHALLENGE (Comparison Study of Cilostazol and Aspirin on Changes in Volume of Cerebral Small Vessel Disease White Matter Changes) database was analyzed. Out of 256 subjects, 189 participants with a follow-up brain scan were included in the analysis. The linear mixed-effect model was used to compare the 2-year changes in the number of CMBs between me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…This anatomical link between large and small artery pathology is consistent with either shared pathophysiological mechanisms or vulnerability rather than simply shared risk factors [ 29 , 31 , 36 , 43 ]. Importantly, results from meta-regression of gender heterogeneity on the influencing of CMBs in AIS patients with IADE showed that gender might not affect the incidence or burden of CMBs, in agreement with previous studies [ 44 , 45 ]. Even though we did not find evidence that the heterogeneity in the relationship between IADE and CMBs is driven by differences in hypertension in the meta-regression analysis, previous studies have emphasised the strong association between IADE and the presence of CMBs after adjusting for age, sex, and hypertension [ 13 ].…”
Section: Discussionsupporting
confidence: 91%
“…This anatomical link between large and small artery pathology is consistent with either shared pathophysiological mechanisms or vulnerability rather than simply shared risk factors [ 29 , 31 , 36 , 43 ]. Importantly, results from meta-regression of gender heterogeneity on the influencing of CMBs in AIS patients with IADE showed that gender might not affect the incidence or burden of CMBs, in agreement with previous studies [ 44 , 45 ]. Even though we did not find evidence that the heterogeneity in the relationship between IADE and CMBs is driven by differences in hypertension in the meta-regression analysis, previous studies have emphasised the strong association between IADE and the presence of CMBs after adjusting for age, sex, and hypertension [ 13 ].…”
Section: Discussionsupporting
confidence: 91%
“…6 C, D). However, age and sex are known to influence both VEGFA plasma levels and BBB integrity [ 9 , 53 , 62 , 68 ]. After adjustment for these covariates we found a significant the relationship between VEGFA plasma levels and BBB leakage rate (K i ) in the NAWM in patients ( p = 0.044, Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…), our results showing sex differences in migratory responses to injury could have functional implications. Human studies are rather mixed but show that males diagnosed with cerebral amyloid angiopathy ( 87 ), mild cognitive impairment, or Alzheimer disease ( 88 ), have significantly more cerebral microbleeds than females ( 89 ), whereas females with small vessel disease have increased microbleed burden ( 90 ). In rodents, the picture appears more consistent where female mice exhibit more abundant microbleeds than males in mouse models of Alzheimer disease ( 91 ) or cerebral amyloid angiopathy ( 92 ).…”
Section: Discussionmentioning
confidence: 99%